Attenuation of CCl4-induced hepatic fibrosis in mice by vaccinating against TGF-β1. - Xiaobao Fan; Qiannan Zhang; Shuang Li; Yifei Lv; Houqiang Su; Huiping Jiang; Zhiming Hao (PLoS ONE, 2013)
Transforming growth factor β1 (TGF-β1) is the pivotal pro-fibrogenic cytokine in hepatic fibrosis. Reducing the over-produced expression of TGF-β1 or blocking its signaling pathways is considered to be a promising therapeutic strategy for hepatic fibrosis. In this study, we evaluated the feasibility of attenuating hepatic fibrosis by vaccination against TGF-β1 with TGF-β1 kinoids. Two TGF-β1 kinoid vaccines were prepared by cross-linking TGF-β1-derived polypeptides (TGF-β1(25)-[41-65] and TGF-β1(30)-[83-112]) to keyhole limpet hemocyanin (KLH). Immunization with the two TGF-β1 kinoids efficiently elicited the production of high-levels of TGF-β1-specific antibodies against in BALB/c mice as tested by enzyme-linked immunosorbent assay (ELISA) and Western blotting. The antisera neutralized TGF-β1-induced growth-inhibition on mink lung epithelial cells (Mv1Lu) and attenuated TGF-β1-induced Smad2/3 phosphorylation, α-SMA, collagen type 1 alpha 2 (COL1A2), plasminogen activator inhibitor-1 (PAI-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1) expression in the rat hepatic stellate cell (HSC) line, HSC-T6. Vaccination against TGF-β1 with the kinoids significantly suppressed CCl4-induced collagen deposition and the expression of α-SMA and desmin, attenuated hepatocyte apoptosis and accelerated hepatocyte proliferation in BALB/c mice. These results demonstrated that immunization with the TGF-β1 kinoids efficiently attenuated CCl4-induced hepatic fibrosis and liver injury. Our study suggests that vaccination against TGF-β1 might be developed into a feasible therapeutic approach for the treatment of chronic fibrotic liver diseases.